Direct synthesis of alkenyl iodides via indium-catalyzed iodoalkylation of alkynes with alcohols and aqueous HI. Issue 17 (12th April 2018) - Wu, Chao; Wang, Zheng; Hu, Zhan; Zeng, Fei; Zhang, Xing-Yu; Cao, Zhong; Tang, Zilong; He, Wei-Min; Xu, Xin-Hua
Abstract : A simple and efficient method has been developed for the synthesis of alkenyl iodides through indium-catalyzed iodoalkylation of alkynes with alcohols and aqueous HI under mild conditions. Abstract : A convenient and efficient indium-catalyzed approach to synthesize alkenyl iodides has been developed through direct iodoalkylation of alkynes with alcohols and aqueous HI under mild conditions. This catalytic protocol offers an attractive approach for the synthesis of a diverse range of alkenyl iodides in good to excellent yields.